Diversity and Population Status of Non-Timber Forest Products (NTFPS) in Community Forests of Dovan, Palpa, Nepal - Gubhaju, Munesh R.; Ghimire, Suresh K. (Journal of Natural History Museum, 2009)
Patterns of diversity and distribution of non-timber forest product species (NTFPs) were studied in three community forests of Dovan VDC, Palpa. Richness of total plant species and NTFP species was compared in different community forests in relation to forest size, altitude, human disturbance and other physical factors. A total of 143 vascular plant species have been documented from the study area among which 114 species were identified as potentially useful species (NTFPs). The gamma diversity of all species as well as NTFP species was high in large-sized community forest and low in smaller-sized community forest indicating area-based increase in habitat heterogeneity in maintaining overall landscape level species diversity. But species richness (alpha diversity) showed pattern related more with the level of human disturbance associated with the management practices. Key words: Species richness; Alpha diversity; Beta diversity; Gamma diversity; Altitude; Disturbance. Journal of Natural History Museum Vol. 24, 2009 Page: 21-46